High-conductivity lithium iron phosphate positive electrode material and preparation method thereof

By depositing and chemically reacting on the surface of lithium iron phosphate positive electrode material, the problem of poor conductivity of lithium iron phosphate positive electrode material in high-ratio lithium ion batteries is solved, and the material conductivity improvement and the performance of lithium ion batteries are optimized.

CN120199794APending Publication Date: 2025-06-24XIAN MODERN CHEM RES INST
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510268003.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-03-07
Publication Date
2025-06-24

AI Technical Summary

Technical Problem

Lithium iron phosphate positive electrode material has poor conductivity in high-speed use scenarios in lithium-ion batteries, resulting in poor performance.

Method used

By depositing disilane on the surface of the lithium iron phosphate positive electrode material and chemically reacting with tungsten hexafluoride to form a tungsten film, the thickness of the tungsten film is accurately controlled using atomic layer deposition technology.

Benefits of technology

The highly uniform dispersion and precise and controllable coating of tungsten on the surface of lithium iron phosphate positive electrode material are achieved, which significantly improves the material's conductivity and the high-rate performance of lithium-ion batteries.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120199794A_ABST
    Figure CN120199794A_ABST
Patent Text Reader

Abstract

The invention provides a high-conductivity lithium iron phosphate positive electrode material and a preparation method thereof, and the method comprises the following steps: depositing disilane on the surface of the lithium iron phosphate positive electrode material, and carrying out chemical reaction on the deposited disilane and a tungsten source to generate a tungsten film. The tungsten source is tungsten hexafluoride. The deposition mode is atomic layer deposition, and the deposition period is 1-30. Tungsten is highly uniformly dispersed on the surface of the lithium iron phosphate positive electrode material, compared with a traditional method that the surface of the lithium iron phosphate positive electrode material is coated with carbon, higher conductivity is achieved, meanwhile, the surface of the lithium iron phosphate positive electrode material is highly uniformly deposited and coated with tungsten, and the thickness of a tungsten film is accurate and adjustable. The preparation method for depositing and coating tungsten on the surface of the lithium iron phosphate positive electrode material is simple, high in automation degree and very good in repeatability; from the perspective of easy preparation, low cost and high rate performance, the invention has a very good application prospect in the field of lithium ion batteries.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of nano energy materials, relates to a lithium iron phosphate cathode material, and specifically relates to a high-conductivity lithium iron phosphate cathode material and a preparation method thereof. Background Art

[0002] As a commonly used cathode material for lithium-ion batteries, due to the poor conductivity of lithium iron phosphate material itself, the performance of lithium iron phosphate material is poor in high-rate use scenarios of lithium-ion batteries. In the prior art, the method to improve the conductivity of lithium iron phosphate cathode material is to carry out carbon modification by solid-state grinding or high-temperature pyrolysis. There are problems in these modification methods that the carbon added has uneven surface coating on the cathode material and the thickness of the coating layer cannot be accurately controlled.

[0003] Uneven coating will lead to the problem of uneven stress during charge and discharge of the modified lithium-ion battery, resulting in particle cracking. The performance improved by coating modification is closely related to the type and thickness of the surface coating layer. The coating material with strong conductivity and high lithium-ion transport rate can improve the rate performance of lithium-ion batteries at a certain coating thickness. If the coating thickness is too thin, the performance improvement will not be obvious. If the coating thickness is too thick, the performance of lithium-ion batteries will be lower than that before modification. Summary of the Invention

[0004] Aiming at the deficiencies of the prior art, the purpose of the present invention is to provide a high-conductivity lithium iron phosphate cathode material and a preparation method thereof, and solve the technical problem that the performance of the lithium iron phosphate cathode material in the prior art needs to be further improved when used to prepare high-rate lithium-ion batteries.

[0005] To solve the above technical problems, the present invention is implemented by adopting the following technical solutions:

[0006] A preparation method of a lithium iron phosphate cathode material, which first deposits disilane on the surface of the lithium iron phosphate cathode material, and then makes the deposited disilane react chemically with a tungsten source to generate a tungsten thin film.

[0007] The present invention also has the following technical features:

[0008] Specifically, the tungsten source is tungsten hexafluoride.

[0009] Specifically, the deposition method is atomic layer deposition, and the number of deposition cycles is 1-30.

[0010] Preferably, the method specifically includes the following steps:

[0011] Step 1, lay the lithium iron phosphate cathode material flat on the sample stage and then place it in the reaction chamber of the atomic layer deposition equipment. Seal the outlet of the reaction chamber, and use a mechanical vacuum pump to evacuate the air in the reaction chamber.

[0012] Step 2: Set the temperature and heat up to make the temperature in the reaction chamber 250 °C.

[0013] Step 3: Introduce an inert carrier gas into the reaction chamber from the inlet of the atomic layer deposition equipment, and evacuate with a mechanical pump at the outlet to make the vacuum degree in the reaction chamber stable at 20 - 150 Pa.

[0014] Step 4: Close the evacuation port of the mechanical pump, inject disilane into the reaction chamber through the inlet of the atomic layer deposition equipment. The flow rate of the disilane carrier gas is V1, the injection time is t1, and the free diffusion time is t2.

[0015] Step 5: Open the evacuation port of the mechanical pump, introduce an inert carrier gas with a flow rate of V all into the reaction chamber to blow away the physically adsorbed disilane on the surface of the lithium iron phosphate cathode material, and the blowing - away time is t3.

[0016] Step 6: Close the evacuation port of the mechanical pump, inject a tungsten source into the reaction chamber through the inlet of the atomic layer deposition equipment. The flow rate of the tungsten source carrier gas is V2, the injection time is t4, and the free diffusion time is t5.

[0017] Step 7: Open the evacuation port of the mechanical pump, introduce an inert carrier gas with a flow rate of V all into the reaction chamber to blow away the by - products and excessive tungsten source on the surface of the lithium iron phosphate cathode material, and the blowing - away time is t6.

[0018] Step 8: Steps 4 to 7 are one cycle of atomic layer deposition of tungsten thin film. Repeat steps 4 to 7. By increasing the deposition cycles of atomic layer deposition, control different deposition thicknesses to prepare lithium iron phosphate cathode materials with different deposition cycle numbers, denoted as nW@lithium iron phosphate cathode material, where n is the number of deposition cycles.

[0019] Specifically, in step 3, the inert carrier gas is nitrogen or argon.

[0020] In step 4, the disilane carrier gas is nitrogen or argon; V1 is 100 ml / min; t1 is 1 - 2 s; t2 is 30 s.

[0021] In step 5, V all is 200 ml / min; the inert carrier gas is nitrogen or argon; t3 is 120 s.

[0022] In step 6, the tungsten source carrier gas is nitrogen or argon; V2 is 100 ml / min; t4 is 1 - 2 s; t5 is 30 s.

[0023] In step 7, V allis 200 ml / min; the inert carrier gas is nitrogen or argon; t6 is 120 s.

[0024] The present invention also protects a lithium iron phosphate cathode material, including the lithium iron phosphate cathode material, and a tungsten thin film is coated on the lithium iron phosphate cathode material.

[0025] Specifically, the preparation method of the lithium iron phosphate cathode material is as follows: first deposit disilane on the surface of the lithium iron phosphate cathode material, and then make the deposited disilane react chemically with a tungsten source to generate a tungsten thin film.

[0026] Preferably, the particle size of the lithium iron phosphate cathode material is 1 μm to 30 μm.

[0027] Preferably, the thickness of the tungsten thin film is 0.1 nm to 3 nm.

[0028] Compared with the prior art, the present invention has the following technical effects:

[0029] (Ⅰ) In the present invention, tungsten is highly uniformly dispersed on the surface of the lithium iron phosphate cathode material, has a higher conductivity compared with the traditional coating of carbon on the surface of the lithium iron phosphate cathode material. At the same time, tungsten is highly uniformly deposited and coated on the surface of the lithium iron phosphate cathode material, and the thickness of the tungsten thin film can be accurately adjusted.

[0030] (Ⅱ) In the present invention, atomic layer deposition is used to deposit tungsten on the surface of the lithium iron phosphate cathode material. The lithium iron phosphate cathode materials with different tungsten deposition cycles are assembled into lithium-ion batteries and subjected to high-rate performance tests, and excellent high-rate performance is obtained, further proving that the tungsten-coated lithium iron phosphate cathode material has a very broad application prospect in high-rate lithium-ion batteries.

[0031] (Ⅲ) The preparation method of depositing and coating tungsten on the surface of the lithium iron phosphate cathode material in the present invention is simple, has a high degree of automation, and has very good repeatability; considering from the aspects of easy preparation, low cost, and high-rate performance, the present invention has a very good application prospect in the field of lithium-ion batteries. Description of the Drawings

[0032] Figure 1(a) is a high-rate test chart of the lithium iron phosphate cathode material in the present invention after being assembled into a lithium-ion battery.

[0033] Figure 1(b) is a high-rate test chart of the 1W@ lithium iron phosphate cathode material in the present invention after being assembled into a lithium-ion battery.

[0034] Figure 1(c) is a high-rate test chart of the 2W@ lithium iron phosphate cathode material in the present invention after being assembled into a lithium-ion battery.

[0035] Figure 1(d) is a high-rate test chart of the 30W@ lithium iron phosphate cathode material in the present invention after being assembled into a lithium-ion battery.

[0036] Figure 2 It is a transmission electron microscope image of a 30W@lithium iron phosphate cathode material.

[0037] Figure 3(a) is an XPS image of a 2W@lithium iron phosphate cathode material.

[0038] Figure 3(b) is the W 4f spectrum of a 2W@lithium iron phosphate cathode material.

[0039] The following further elaborates on the specific content of the present invention in conjunction with the accompanying drawings and embodiments. Specific Embodiments

[0040] It should be noted that all raw materials and instruments in the present invention, unless otherwise specified, are all raw materials and instruments known in the prior art. For example, the lithium iron phosphate cathode material uses a known lithium iron phosphate cathode material, disilane uses a known disilane, and the atomic layer deposition equipment uses a known atomic layer deposition equipment.

[0041] The technical concept of the present invention is that atomic layer deposition technology is a deposition coating technology that can deposit and coat on the surface of nanoparticles, with the characteristics of high precision and high uniformity. The prior art has confirmed that atomic layer deposition technology can deposit and modify the surface of the cathode material of lithium-ion batteries, improving the performance of lithium-ion batteries.

[0042] Generally, the higher the temperature treatment, the higher the conductivity of the carbon obtained. Currently, the temperature for preparing carbon by thermal decomposition of organic substances coating carbon on the lithium iron phosphate cathode material is below 300°C, and the temperature for preparing conductive carbon black is above 1200°C. The conductivity of conductive carbon black is 0.01 - 0.1 S / cm. The tungsten metal film prepared by atomic layer deposition has a higher conductivity because its atomic arrangement is more compact than that of metallic tungsten in nature. The conductivity of metallic tungsten in nature is 0.2 S / cm. Therefore, using atomic layer deposition technology to prepare a metallic tungsten film on the surface of the lithium iron phosphate cathode material can achieve both high-uniformity deposition coating and high-precision controllable coating thickness, and improve the conductivity of the lithium iron phosphate cathode material.

[0043] In the present invention, tungsten-coated lithium iron phosphate cathode material means that tungsten is deposited on the surface of the lithium iron phosphate cathode material.

[0044] In the present invention, the reaction process of the chemical reaction is as follows:

[0045]

[0046] Following the above technical solution, the following specific embodiments of the present invention are given. It should be noted that the present invention is not limited to the following specific embodiments, and all equivalent transformations made on the basis of the technical solution of this application fall within the protection scope of the present invention.

[0047] Example 1:

[0048] This example provides a method for preparing a lithium iron phosphate cathode material with high electrical conductivity. In this method, disilane is first deposited on the surface of the lithium iron phosphate cathode material, and then the deposited disilane reacts chemically with a tungsten source to form a tungsten thin film.

[0049] The tungsten source is tungsten hexafluoride.

[0050] The deposition method is atomic layer deposition, and the number of deposition cycles is 1.

[0051] This method specifically includes the following steps:

[0052] Step 1: Place the lithium iron phosphate cathode material flat on the sample stage and then place it in the reaction chamber of the atomic layer deposition equipment. Seal the outlet of the reaction chamber, and use a mechanical vacuum pump to evacuate the air in the reaction chamber.

[0053] Step 2: Set the temperature and heat up to make the temperature in the reaction chamber 250 °C.

[0054] Step 3: Introduce an inert carrier gas into the reaction chamber from the inlet of the atomic layer deposition equipment, and use a mechanical pump to pump air at the outlet to make the vacuum degree in the reaction chamber stable at 80 Pa.

[0055] In Step 3, the inert carrier gas is argon.

[0056] Step 4: Close the mechanical pump air extraction port, and inject disilane into the reaction chamber through the inlet of the atomic layer deposition equipment. The flow rate of the disilane carrier gas is V1, the injection time is t1, and the free diffusion time is t2.

[0057] In Step 4, the disilane carrier gas is argon; V1 is 100 ml / min; t1 is 2 s; t2 is 30 s.

[0058] In this example, the free diffusion time is 30 s to allow disilane to undergo sufficient chemisorption on the surface of the lithium iron phosphate cathode material.

[0059] Step 5: Open the mechanical pump air extraction port, and introduce an inert carrier gas with a flow rate of V all into the reaction chamber to blow off the physically adsorbed disilane on the surface of the lithium iron phosphate cathode material. The blowing-off time is t3.

[0060] In Step 5, V all is 200 ml / min; the inert carrier gas is argon; t3 is 120 s.

[0061] Step 6: Close the mechanical pump air extraction port, and inject the tungsten source into the reaction chamber through the inlet of the atomic layer deposition equipment. The flow rate of the tungsten source carrier gas is V2, the injection time is t4, and the free diffusion time is t5.

[0062] In Step 6, the tungsten source carrier gas is argon; V2 is 100 ml / min; t4 is 2 s; t5 is 30 s.

[0063] In this embodiment, the free diffusion time is 30 s, enabling a chemical reaction between the W source and the ethylsilane chemisorbed on the surface of the lithium iron phosphate cathode material.

[0064] Step 7: Open the pumping port of the mechanical pump and introduce an inert carrier gas with a flow rate of V all into the reaction chamber to blow away the by-products and excessive tungsten source on the surface of the lithium iron phosphate cathode material. The blowing-away time is t6.

[0065] In Step 7, V all is 200 ml / min; the inert carrier gas is argon; t6 is 120 s.

[0066] Step 8: Steps 4 to 7 are one cycle of atomic layer deposition of tungsten thin film. Repeat Steps 4 to 7. By increasing the deposition cycles of atomic layer deposition, different deposition thicknesses are controlled to prepare high-conductivity lithium iron phosphate cathode materials with different numbers of deposition cycles, denoted as nW@lithium iron phosphate cathode materials, where n is the number of deposition cycles.

[0067] In this embodiment, the number of deposition cycles of atomic layer deposition is 1, and the obtained high-conductivity lithium iron phosphate cathode material is denoted as 1W@lithium iron phosphate cathode material.

[0068] This embodiment also provides a lithium iron phosphate cathode material, including a lithium iron phosphate cathode material with a tungsten thin film coated thereon.

[0069] The preparation method of the lithium iron phosphate cathode material is as follows: First, deposit ethylsilane on the surface of the lithium iron phosphate cathode material, and then cause the deposited ethylsilane to react chemically with the tungsten source to form a tungsten thin film.

[0070] The particle size of the lithium iron phosphate cathode material is 15 μm.

[0071] The thickness of the thin film is 2 nm.

[0072] This embodiment also provides a modified lithium-ion battery, which is prepared from the 1W@lithium iron phosphate cathode material. The preparation method of the modified lithium-ion battery specifically includes the following steps:

[0073] Step 1: Place the 1W@lithium iron phosphate cathode material, PVDF binder, and carbon black in a mass ratio of 8:1:1 in a dispersant and stir for 4 h to obtain a stirred slurry.

[0074] Step 2: Coat the stirred slurry obtained in Step 1 on an aluminum foil current collector, and then dry it in an oven at 90 °C for 10 h.

[0075] Step 3: Cut the dried electrode sheets into required sizes and weigh them for quality.

[0076] Step 4: Assemble the lithium iron phosphate electrode sheets modified with tungsten, shrapnel, gaskets, lithium sheets, positive electrode cases, negative electrode cases, electrolyte, and separator into button-type lithium-ion batteries in an argon environment.

[0077] Example 2:

[0078] This example provides a preparation method for a high-conductivity lithium iron phosphate cathode material. The preparation method for this high-conductivity lithium iron phosphate cathode material is the same as that in Example 1, except that: in Step 8, the number of deposition cycles of atomic layer deposition is 2, that is, the obtained high-conductivity lithium iron phosphate cathode material is denoted as 2W@lithium iron phosphate cathode material.

[0079] This example also provides a high-conductivity lithium iron phosphate cathode material, which is prepared by the preparation method for the high-conductivity lithium iron phosphate cathode material in this example.

[0080] This example also provides a modified lithium-ion battery, which is prepared by the 2W@lithium iron phosphate cathode material. The preparation method for this modified lithium-ion battery is the same as that in Example 1, except that: the 1W@lithium iron phosphate cathode material in Step 1 is changed to 2W@lithium iron phosphate cathode material.

[0081] Example 3:

[0082] This example provides a preparation method for a high-conductivity lithium iron phosphate cathode material. The preparation method for this high-conductivity lithium iron phosphate cathode material is the same as that in Example 1, except that: in Step 8, the number of deposition cycles of atomic layer deposition is 30, that is, the obtained high-conductivity lithium iron phosphate cathode material is denoted as 30W@lithium iron phosphate cathode material.

[0083] This example also provides a high-conductivity lithium iron phosphate cathode material, which is prepared by the preparation method for the high-conductivity lithium iron phosphate cathode material in this example.

[0084] This example also provides a modified lithium-ion battery, which is prepared by the 30W@lithium iron phosphate cathode material. The preparation method for this modified lithium-ion battery is the same as that in Example 1, except that: the 1W@lithium iron phosphate cathode material in Step 1 is changed to 30W@lithium iron phosphate cathode material.

[0085] Comparative Example 1:

[0086] In this example, a lithium-ion battery is provided. This lithium-ion battery is prepared from a lithium iron phosphate cathode material. The preparation method of this lithium-ion battery is the same as that of the modified lithium-ion battery in Example 1, except that: the 1W@ lithium iron phosphate cathode material in Step 1 is changed to a lithium iron phosphate cathode material, that is, the surface of the lithium iron phosphate cathode material in this example is not coated with a tungsten thin film.

[0087] The coin-type lithium-ion batteries prepared in Example 1, Example 2, Example 3, and Comparative Example 1 were respectively subjected to high-rate tests on a battery performance tester. The rate test conditions of 0.1C - 0.2C - 0.5C - 2C - 5C - 12C - 20C were set for the test.

[0088] Comparison Figures 1(a) to 1(d) It can be seen later that the lithium iron phosphate cathode material modified with tungsten (taking the 2W@ lithium iron phosphate cathode material as an example) has excellent performance in the high-rate test after being assembled into a lithium-ion battery, showing specific capacities of 130 mAh / g, 118 mAh / g, and 95 mAh / g at 5C, 12C, and 20C respectively. The results are shown in Figure 1(c); the unmodified lithium iron phosphate cathode material has basically no capacity after 5C, and the results are shown in Figure 1(a).

[0089] The 30W@ lithium iron phosphate cathode material was tested by transmission electron microscopy, and the results are as Figure 2 shown. It can be seen from Figure 2 that tungsten is uniformly coated on the surface of the lithium iron phosphate cathode material with a thickness of 4 nm. The deposited and coated tungsten does not change the morphology and size of the lithium iron phosphate cathode material itself.

[0090] It can be seen from Figure 3(a) and Figure 3(b) that tungsten elements have a similar distribution to iron elements, indicating that tungsten elements are uniformly distributed on the surface of the lithium iron phosphate cathode material.

[0091] The conductivity of the unmodified lithium iron phosphate cathode material in Comparative Example 1 and the tungsten-modified lithium iron phosphate cathode material in Example 2 was compared, repeated three times, and the average value was calculated. The results are shown in Table 1.

[0092] Table 1 Comparison of the conductivity of the lithium iron phosphate cathode materials in Comparative Example 1 and Example 2

[0093] The first group The second group The third group Average value Comparative Example 1 34 Ω / cm 35 Ω / cm 35 Ω / cm 34.67 Ω / cm Example 2 26 Ω / cm 26 Ω / cm 26 Ω / cm 26.00 Ω / cm

[0094] Table 1 shows that the resistivity of the lithium iron phosphate cathode material modified with tungsten coating is lower than that of the unmodified lithium iron phosphate cathode material, proving that the lithium iron phosphate cathode material modified with tungsten coating has good conductivity.

Claims

1. A method for preparing a lithium iron phosphate positive electrode material, characterized in that: The method first deposits disilane on the surface of the lithium iron phosphate positive electrode material, and then allows the deposited disilane to react chemically with a tungsten source to generate a tungsten film.

2. The method for preparing the lithium iron phosphate positive electrode material according to claim 1, characterized in that: The tungsten source is tungsten hexafluoride.

3. The method for preparing the lithium iron phosphate positive electrode material according to claim 2, characterized in that: The deposition method is atomic layer deposition, and the number of deposition cycles is 1 to 30.

4. The method for preparing the lithium iron phosphate positive electrode material according to claim 3, characterized in that: The method specifically comprises the following steps: Step 1: Lay the lithium iron phosphate cathode material flat on the sample table and place it in the reaction chamber of the atomic layer deposition equipment, seal the outlet of the reaction chamber, and use a mechanical vacuum pump to evacuate the air in the reaction chamber; Step 2: Set the temperature and increase the temperature so that the temperature in the reaction chamber is 250°C; Step 3: Introduce an inert carrier gas into the reaction chamber from the inlet of the atomic layer deposition equipment, and use a mechanical pump to evacuate the gas at the outlet to stabilize the vacuum degree in the reaction chamber at 20-150 Pa; Step 4, close the mechanical pump exhaust port, and inject disilane into the reaction chamber through the inlet of the atomic layer deposition equipment. The disilane carrier gas flow rate is V1, the injection time is t1, and the free diffusion time is t2; Step 5: Open the mechanical pump air outlet and set the flow rate to V all An inert carrier gas is introduced into the reaction chamber to blow away the disilane physically adsorbed on the surface of the lithium iron phosphate positive electrode material, and the blowing time is t3; Step 6, close the mechanical pump exhaust port, inject the tungsten source into the reaction chamber through the inlet of the atomic layer deposition equipment, the tungsten source carrier gas flow rate is V2, the injection time is t4, and the free diffusion time is t5; Step 7: Open the mechanical pump air outlet and set the flow rate to V all The inert carrier gas is introduced into the reaction chamber to blow away the byproducts and excess tungsten source on the surface of the lithium iron phosphate positive electrode material. The blowing time is t6; Step eight, steps four to seven are one cycle of atomic layer deposition of tungsten film. Steps four to seven are repeated. By increasing the deposition cycle of atomic layer deposition and controlling different deposition thicknesses, lithium iron phosphate positive electrode materials with different deposition cycle numbers are prepared, which are recorded as nW@lithium iron phosphate positive electrode materials, where n is the number of deposition cycles.

5. The method for preparing the lithium iron phosphate positive electrode material according to claim 4, characterized in that: In step 3, the inert carrier gas is nitrogen or argon; In step 4, the disilane carrier gas is nitrogen or argon; the V1 is 100 ml / min; the t1 is 1 to 2 s; and the t2 is 30 s; In step 5, the V all is 200ml / min; the inert carrier gas is nitrogen or argon; the t3 is 120s; In step 6, the tungsten source carrier gas is nitrogen or argon; the V2 is 100 ml / min; the t4 is 1-2 s; the t5 is 30 s; In step 7, the V all is 200ml / min; the inert carrier gas is nitrogen or argon; and the t6 is 120s.

6. A lithium iron phosphate positive electrode material, comprising a lithium iron phosphate positive electrode material, characterized in that: The lithium iron phosphate positive electrode material is coated with a tungsten film.

7. The lithium iron phosphate positive electrode material according to claim 6, characterized in that The preparation method of the lithium iron phosphate positive electrode material is: firstly depositing disilane on the surface of the lithium iron phosphate positive electrode material, and then making the deposited disilane react chemically with a tungsten source to form a tungsten film.

8. The lithium iron phosphate positive electrode material according to claim 6, characterized in that The particle size of the lithium iron phosphate positive electrode material is 1 μm to 30 μm.

9. The lithium iron phosphate positive electrode material according to claim 6, characterized in that: The thickness of the tungsten film is 0.1nm-3nm.